Aberrant expression of miR‐218 and miR‐204 in human mesial temporal lobe epilepsy and hippocampal sclerosis—Convergence on axonal guidance. Issue 12 (19th November 2014) - Kaalund, Sanne S.; Venø, Morten T.; Bak, Mads; Møller, Rikke S.; Laursen, Henning; Madsen, Flemming; Broholm, Helle; Quistorff, Bjørn; Uldall, Peter; Tommerup, Niels; Kauppinen, Sakari; Sabers, Anne; et al.
Summary Objective Mesial temporal lobe epilepsy (MTLE) is one of the most common types of the intractable epilepsies and is most often associated with hippocampal sclerosis (HS), which is characterized by pronounced loss of hippocampal pyramidal neurons. microRNAs (miRNAs) have been shown to be dysregulated in epilepsy and neurodegenerative diseases, and we hypothesized that miRNAs could be involved in the pathogenesis of MTLE and HS. Methods miRNA expression was quantified in hippocampal specimens from human patients using miRNA microarray and quantitative real‐time polymerase chain reaction RT‐PCR, and by RNA‐seq on fetal brain specimens from domestic pigs. In situ hybridization was used to show the spatial distribution of miRNAs in the human hippocampus. The potential effect of miRNAs on targets genes was investigated using the dual luciferase reporter gene assay. Results miRNA expression profiling showed that 25 miRNAs were up‐regulated and 5 were down‐regulated in hippocampus biopsies of MTLE/HS patients compared to controls. We showed that miR‐204 and miR‐218 were significantly down‐regulated in MTLE and HS, and both were expressed in neurons in all subfields of normal hippocampus. Moreover, miR‐204 and miR‐218 showed strong changes in expression during fetal development of the hippocampus in pigs, and we identified four target genes, involved in axonal guidance and synaptic plasticity, ROBO1, GRM1, SLC1A2, and GNAI2, as bona fide targets of miR‐218. GRM1 was also shown to be a direct target of miR‐204. Significance miR‐204 and miR‐218 are developmentally regulated in the hippocampus and may contribute to the molecular mechanisms underlying the pathogenesis of MTLE and HS.